High capacity crystal immobilization of U5+ and U6+ by ZrSiO4 ceramics. Issue 8 (15th April 2023) - Xiong, Yingwei; Zhang, Yanming; Li, Jiajing; Dan, Hui; Ding, Yi
Abstract: ZrSiO4 -based ceramics have been considered as one of the candidate nuclear waste forms, while the immobilization behavior of mixed-valent uranium in the structure of the ceramics was unclear. Herein, ZrSiO4 –U ceramics with a general formula of Zr1-4 x (U 6+ x U 5+ 2 x )SiO4 were designed and synthesized. The evolutions of phase and microstructure depending on the content of U were investigated. The ceramics with 0 ≤ x < 0.04 showed a single ZrSiO4 phase, while U3 O8 phase was detected when x ≥ 0.04. The results demonstrated that the solubility limit of U in ZrSiO4 ceramic was up to 1.51 at.% or 11.06 wt%. The calculated lattice parameters increased with the increase of U content. The increased parameters provided the evidence of the immobilization of both U 5+ and U 6+ into ZrSiO4 crystal lattice by replacing Zr 4+ . Furthermore, the obtained ZrSiO4 –U ceramics exhibited good aqueous durability (∼10 −5 g m −2 d −1 ). The results indicated that ZrSiO4 -based ceramics can be employed to effectively immobilize mixed-valent U.